Dual-hazard control mechanism of burst-prone and spontaneous combustion coalface considering effect of retreat speed. (November 2021) - Zhang, Shizhong; Fan, Gangwei; Jiang, Shuyin; Fan, Zhanglei; Li, Shaodong; Ni, Huining
Abstract: For longwall top coal caving coalface characterized by strong rock burst tendency and high risk of spontaneous combustion, retreat speed is one of the key factors to induce the rock burst and spontaneous combustion of residual coal in goaf. A high retreat speed may lead to violent roof activity and impact dynamic load, which aggravates the tendency of rock burst. A low retreat speed may lead to spontaneous combustion of residual coal in goaf due to long time exposure to aerobic environment. In this study, the characteristics of overburden stress distributions, energy release laws, and the evolving laws of the oxidation and temperature rising zones in the goaf under different retreat speeds are analyzed. The spontaneous combustion coefficient of residual coal Q s is defined. What is more, the dual-hazard control mechanism of rock burst and spontaneous combustion of residual coal considering effect of retreat speed is put forward. The results show that the energy release of the stope with low retreat speed is stable, while that with high retreat speed appears obvious fluctuation phenomenon. With the increase of retreat speed, the relative stress concentration coefficient increases exponentially, while the spontaneous combustion coefficient of residual coal in goaf decreases exponentially. According to the curve of retreat speed and relative stress concentration coefficient and curve of retreat speed and spontaneous combustion coefficient, the reasonable operating interval and optimal operating point of retreat speed in strong rock burst tendency and easy spontaneous combustion coal seam can be determined. Highlights: A high retreat speed may lead to rock burst for strong burst-prone coalface. A low retreat speed may lead to spontaneous combustion of residual coal in goaf. Dual-hazard control considering the retreat speed should be paid more attention. The dual-hazard control based on the concept of operating point is put forward.